Combining spinal neuromodulation and activity based neurorehabilitation therapy improves sensorimotor function in cerebral palsy - Sachdeva, Rahul; Girshin, Kristin; Shirkhani, Yousef; Gad, Parag; Edgerton, V. Reggie (Frontiers in Rehabilitation Sciences, 2023)
Motor dysfunction in individuals with cerebral palsy (CP) such as the inability to initiate voluntary movements, walking with compensatory movement patterns, and debilitating spasticity is due to the aberrant neural connectivity between the brain and spinal cord. We tested the efficacy of noninvasive spinal cord neuromodulation (SCiPTM, SpineX Inc.) with activity-based neurorehabilitation therapy (ABNT) in improving the sensorimotor function in six children with CP. Children received 8 weeks of either SCiPTM or sham therapy with ABNT (n=3 per group). At the end of 8 weeks, all participants received 8 weeks of SCiPTM therapy with ABNT. Follow up assessments were done at week 26 (10 weeks after the last therapy session). Sensorimotor function was measured by the Gross Motor Function Measure 88 (GMFM88) test. We observed minimal change in sham group (mean 6% improvement), however, eight weeks of SCiPTM therapy with ABNT resulted in statistically and clinically relevant improvement in GMFM88 scores (mean 23% increase from baseline). We also observed reduced scores on the modified Ashworth scale only with SCiPTM therapy (-11% vs. +5.53% with sham). Similar improvements were observed in sham group but only after the cross over to SCiPTM therapy group at the end of the first eight weeks. Finally, sixteen weeks of SCiPTM therapy with ABNT resulted in further improvement of GMFM88 score. The improvement in GMFM88 scores were maintained at week 26 (10 weeks after the end of therapy), suggesting a sustained effect of SCiPTM therapy.